2020
DOI: 10.1038/s41467-020-19370-z
|View full text |Cite
|
Sign up to set email alerts
|

ArfB can displace mRNA to rescue stalled ribosomes

Abstract: Ribosomes stalled during translation must be rescued to replenish the pool of translation-competent ribosomal subunits. Bacterial alternative rescue factor B (ArfB) releases nascent peptides from ribosomes stalled on mRNAs truncated at the A site, allowing ribosome recycling. Prior structural work revealed that ArfB recognizes such ribosomes by inserting its C-terminal α-helix into the vacant mRNA tunnel. In this work, we report that ArfB can efficiently recognize a wider range of mRNA substrates, including lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
37
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(40 citation statements)
references
References 72 publications
2
37
1
Order By: Relevance
“…A recent cryo-EM study revealed two intermediate steps of ArfB accommodation to a non-stop complex ( Carbone et al, 2020 ). In the first intermediate the C-terminal tail has already bound to the mRNA entry channel and formed an α-helix, while the NTD is associated with H69 of the 23S rRNA and the flexible GGQ loop is pointed away from the A-site of the 50S subunit ( Figures 4A,B ).…”
Section: Bacterial Ribosome Rescue Systemsmentioning
confidence: 99%
See 4 more Smart Citations
“…A recent cryo-EM study revealed two intermediate steps of ArfB accommodation to a non-stop complex ( Carbone et al, 2020 ). In the first intermediate the C-terminal tail has already bound to the mRNA entry channel and formed an α-helix, while the NTD is associated with H69 of the 23S rRNA and the flexible GGQ loop is pointed away from the A-site of the 50S subunit ( Figures 4A,B ).…”
Section: Bacterial Ribosome Rescue Systemsmentioning
confidence: 99%
“…The second intermediate shows that the NTD is still bound to H69, but is rotated so that the GGQ loop is directed toward the large subunit A-site ( Figure 4C ), priming ArfB for insertion into the PTC to perform hydrolysis. Eventually, the NTD is placed in the A-site of the large subunit and accommodates into the PTC ( Figure 4D ), which is induced upon binding of the NTD ( Gagnon et al, 2012 ; Carbone et al, 2020 ; Chan et al, 2020 ). The GGQ motif adopts an analogous conformation to the GGQ motif of bacterial class I RFs and mediates hydrolysis of the ester bond between the peptide and the P-tRNA.…”
Section: Bacterial Ribosome Rescue Systemsmentioning
confidence: 99%
See 3 more Smart Citations